(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the functional outcome of proximal Humerus fracture in elderly patients treated non operatively versus operatively. Methods: This retrospective Cohort study was conducted in Orthopaedic Department Fazaia Ruth Pfau Medical College PAF Base Faisal Karachi. The medical records of all patients of proximal Humerus fractures fulfilling the inclusion criteria and managed in time period extending from 23rd June 2018 to 25th May 2022 were reviewed. The included subjects were divided into group A(non-operative) and group B(open reduction and internal fixation with Proximal Humerus Internal Locking System).Comparison of functional outcome in both groups at 6th, 12th , and 18th months of follow up was done using American Shoulder and Elbow Score(ASES).P value was calculated using Chi-square test, student t-test and one way ANOVA test. P value <0.05 was considered significant. Results: The records of 92 patients of proximal humerus fractures were reviewed. Group A included 47(51.08%) patients and group B had 45(48.91%) patients. Mean age of group A was 61 ± 4.32 years and group B was 55± 2.33 years. The ASES score for two-part, three-part and four-part fractures at 18th months of follow up period was 79.9,75.2,81.2 in group A and 82.4,77.3 and 83.4 in group B respectively(p>0.05). Radiological union was achieved in average 5±1.2 months in group A and 3±2.1 months in group B(p<0.05). Conclusion: Both non operative and operative treatments of proximal humerus fractures in elderly patients are equally effective in restoring shoulder function. However no significant difference in terms of functional outcome was noted between the two treatment modalities.